Effect of dextrose equivalent of maltodextrin on the stability of emulsified coconut-oil in spray-dried powder. (October 2015) - Matsuura, Tsutashi; Ogawa, Akihiro; Tomabechi, Masaki; Matsushita, Ryo; Gohtani, Shoichi; Neoh, Tze Loon; Yoshii, Hidefumi
Highlights: HCO was encapsulated with different DE of MD and SSE by spray drying. Reconstituted emulsion from MD of DE 10 was less stable than DE 2 and DE 25. A stronger interaction between MD of DE 10 and SSE was suggested by IR and XRD. Abstract: Effect of dextrose equivalent (DE) of maltodextrin (MD) on the reconstituted emulsion stability of emulsified hydrated coconut oil (HCO) in spray-dried powder was investigated. HCO-encapsulated powders were produced with MDs of DE 2, 10, and 25 as wall material and sugar stearic acid esters (SSE) as emulsifier. The reconstituted emulsion from MD of DE 10 was less stable than those from MDs of DE 2 and DE 25. The increase rates of average diameter of reconstituted oil-droplet could be correlated by the zero-order reaction model. By FT-IR and powder X-ray diffraction measurement, spectrum results suggest a stronger interaction between MD of DE 10 and SSE compared to the other two MDs. The interaction between the surfactant and MD is important to select the wall material to form spray-dried powder with a stable reconstituted emulsion.